REGIONAL DISPUTATION BETWEEN NORTH HALMAHERA AND WEST HALMAHERA REGENCIES, 2003-2010 - Mojau, Liliane (UI Scholars Hub, 2021)
Ideally, the proliferation of the administrative region is aimed at improving the welfare of society. In reality, the proliferation of the administrative region often triggers the regional disputation. The regional disputation between the North Halmahera and the West Halmahera regencies is one of the cases that took a long time. There are six villages that contested in this regional disputation, namely Dum-Dum, Gamsungi/Akesahu, Akelamo Kao, Tetewang, Bobane Igo, and Pasir Putih. At first, the government of the North Halmahera and the West Halmahera regencies coordinated to settle their region boundaries. But it develops to the status issue of the six villages: are the six villages part of the North Halmahera or the West Halmahera regencies. This research is aimed at explaining the regional disputation between the North Halmahera and the West Halmahera regencies, 2003-2010. The method used in this research is the historical method, which consists of four stages, namely heuristics, criticism, interpretation, and historiography. The result of this research indicates there are cultural dimension that colored this regional disputation and there is a role of local political elites (DPRD Halmahera Utara).